Spatial variation and ecological risk assessment of heavy metals in mangrove sediments across China. (June 2019) - Shi, Cong; Ding, Huan; Zan, Qijie; Li, Ruili
Abstract: The spatial variations of nine heavy metals in the surface sediments of six Avicennia marina mangrove wetlands across China were investigated. These were Yunxiao, Futian (FT), Zhanjiang, Fangchenggang (FCG), Dongfang (DF), and Dongzhaigang (DZG). Results showed that environmental factors, such as organic matter and sediment grain size, affected heavy metal distribution. The high heavy metal levels in mangrove sediments may be due to their large retention capacity. The dominant heavy metals were Zn, Cr, Pb, Cu, and Cd. Pollution was highest at FT and lowest at FCG. The principal component analysis indicated that Zn, Cd, Cu, Ni, Cr, and Pb were mainly derived from anthropogenic activities. Ecological risk assessments showed that FT was the most polluted area with considerable ecological risk, whereas pollution levels were lowest at FCG, DF, and DZG. This study provides the first integrated analysis of heavy metal pollution of sediments across China. Highlights: First report on heavy metal pollution in mangroves sediments across China Metal pollution risk: Futian > Yunxiao, Zhanjiang > Dongfang, Dongzhaigang, Fangchenggang Heavy metals in mangrove sediments were dominated by Zn, Cr, Pb, Cu, and Cd. Principal component analysis suggests human activity affects Zn, Cd, Cu, Ni, Cr, and Pb in Futian.